Successful selling solutions : test, monitor and constantly improve your selling skills - Clay, Julian (Thorogood, 2003)
This work provides a methodology to enable readers to to test their selling skills and progress in using them. It includes models for forecasting, managing new accounts and monitoring performance. Each stage of the sales cycle is looked at and advice is offered on how to handle each one.